ALL GATHERED TOGETHER: ON THE CONSTRUCTION OF SCIENTIFIC AND TECHNICAL BOOKS IN 15TH-CENTURY ENGLAND - Alonso Almeida, Francisco (International Journal of English Studies, 2009)
In this paper I examine the construction of a corpus of scientific and teclinical books that contain many different items of varied contents. This type of books may be considered as exainples of discourse colonies, in the fashion of earlier studies carried out by Hoey (1986, 2001) and Carroll (2003). Discourse colonies are characterised by the presence of a number of features related to authorship, textual meaning, syntax and communicative function.